A hydrophobic modified self-repairing epoxy resin composite coating and a preparation method and application thereof
Patent Information
- Application Number
- CN202611186854.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-30
AI Technical Summary
但镁合金的标准电极电位为–2.37 V,在含第二相组织中,极易充当阳极,形成强电偶腐蚀
在本发明中,制得的疏水改性自修复环氧树脂复合涂层,操作简便;加入的玄武岩鳞片具有优异的片状屏蔽效应和化学惰性,有效延长了腐蚀介质的扩散路径;负载的离子液体缓蚀剂在涂层受损时能够释放形成保护膜,实现主动自修复。本发明涂层具有较好的防腐性能和优异的自修复性能,有效提高了镁合金的长期耐蚀性能。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of chemical materials and metal corrosion protection technology, specifically relating to a hydrophobic modified self-healing epoxy resin composite coating, its preparation method and application. Background Technology
[0002] Magnesium alloys are widely used in aerospace, transportation, and 3C products due to their advantages such as light weight and good electrical conductivity. However, the standard electrode potential of magnesium alloys is -2.37 V, and in structures containing a second phase, they readily act as anodes, leading to strong galvanic corrosion. Furthermore, the corrosion products of magnesium alloys are porous and loose, which greatly limits their application in extreme environments such as humid, oxidizing, and saline conditions.
[0003] While epoxy (EP) coatings are widely used for metal protection, their inherent hydrophilicity and the micropores formed during curing make them insufficient to completely prevent the penetration of corrosive media during long-term service. Most importantly, EP coatings are passive barrier layers; once mechanical damage occurs, they lack the ability to actively inhibit corrosion propagation. Corrosive media will rapidly penetrate the coating-metal interface through the defects, causing substrate corrosion, coating blistering, and ultimately, overall peeling.
[0004] To overcome the limitations of traditional EP coatings, developing protective coatings that combine "passive physical barrier" and "active intelligent protection" functions is an effective strategy. Imparting hydrophobicity to the coating can effectively reduce the adhesion and penetration of corrosive media on the surface, which can be achieved by lowering the surface energy of the coating and constructing micro-nano rough structures. The self-healing function relies on pre-loading the repair agent onto a nanocarrier and dispersing it in the coating. When the coating is damaged, the repair agent can form a protective film at the corrosion site, achieving active protection.
[0005] Basalt flakes (BS) possess excellent sheet-like shielding effect, chemical inertness, resistance to UV aging, and resistance to acid and alkali corrosion, thus extending the diffusion path of corrosive media. Ionic liquids, characterized by high polarity, low melting point, low toxicity, and high chemical stability, are green and environmentally friendly compounds that can be widely used for corrosion protection of metals. Therefore, loading ionic liquids onto basalt flakes and incorporating them into organic coatings holds promise for imparting better corrosion resistance and self-healing properties to the coatings. Summary of the Invention
[0006] Based on this, in order to address the technical problem of how to improve the corrosion protection and self-healing function of magnesium alloys in extreme environments, this invention provides a hydrophobic modified self-healing epoxy resin composite coating, which has good hydrophobicity and self-healing function.
[0007] Another objective of this invention is to provide a method for preparing and applying the above-mentioned hydrophobically modified self-healing epoxy resin composite coating, wherein the composite coating prepared by this method exhibits excellent long-term corrosion resistance and environmental adaptability.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a hydrophobically modified self-healing epoxy resin composite coating, wherein the composite coating is made of a hydrophobically modified epoxy resin matrix and functional nanofillers dispersed therein; the hydrophobically modified epoxy resin matrix is obtained by chemically modifying epoxy resin with aminopropyl double-terminated polydimethylsiloxane; the functional nanofiller is basalt flakes loaded with ionic liquid corrosion inhibitors.
[0009] As a preferred technical solution, the preparation method of the above-mentioned hydrophobic modified self-healing epoxy resin composite coating includes the following steps: S1. Alkali etching treatment of basalt flakes: Basalt flakes were placed in sodium hydroxide solution and stirred at 80~120 ℃ for 1~4 h. After washing and drying, basalt flakes with alkali etching treatment were obtained. S2. Synthesis of ionic liquid corrosion inhibitor [MCIM][NTf2]: 1-methylimidazolium (C4H6N2) and 11-bromoundecanoic acid (C 11 H 21 [MCIM]Br was obtained by reacting BrO2 in an organic solvent at 30-50 °C for 20-28 h; then [MCIM]Br was reacted with lithium bis(trifluoromethanesulfonyl)imide (C2F6LiNO4S2) in water at 30-50 °C for 8-12 h, followed by rotary evaporation and drying to obtain the ionic liquid corrosion inhibitor [MCIM][NTf2]. S3. Preparation of functional nanofiller BS@MN: The basalt flakes obtained from step S1 with the ionic liquid corrosion inhibitor obtained from step S2 were mixed in tetrahydrofuran, stirred at room temperature for 20-28 h, washed and dried to obtain functional nanofiller BS@MN. S4. Preparation of hydrophobic modified epoxy resin matrix: Bisphenol A diglycidyl ether (DGEBA) and neopentyl glycol diglycidyl ether (NGDE) are mixed evenly, and aminopropyl double-terminated polydimethylsiloxane (NH2-PDMS-NH2) and polyetheramine D230 curing agent are added and mixed evenly to obtain hydrophobic modified epoxy resin matrix (PDMS-EP). S5. Preparation of composite coating: The functional nanofiller BS@MN obtained in step S3 is added to the hydrophobic modified epoxy resin matrix PDMS-EP obtained in step S4, dispersed evenly, and coated onto the pretreated metal substrate surface by spin coating. After curing at room temperature and drying, the composite coating (PDMS-EP / BS@MN) is obtained.
[0010] Specifically, in step S1, the amount of basalt flakes used is 2~5 g, the concentration of sodium hydroxide solution is 2~6 mol / L, the preferred reaction temperature is 90~110 ℃, and the preferred reaction time is 1.5~2.5 h.
[0011] Specifically, in step S2, the molar ratio of 1-methylimidazole to 11-bromoundecanoic acid is 1:0.8~1.2; the organic solvent is tetrahydrofuran, and 3~10 mL of tetrahydrofuran is added for every 1 mmol of 1-methylimidazole. The molar ratio of [MCIM]Br to lithium bis(trifluoromethanesulfonylimide) is 1:0.8~1.2. 3~10 mL of water is added for every 1 mmol of [MCIM]Br.
[0012] Specifically, in step S3, the mass ratio of alkali-etched basalt flakes to ionic liquid corrosion inhibitor is 1:2~4, and the stirring time is preferably 24 h. 80~150 mL of tetrahydrofuran is added for every 1 g of alkali-etched basalt flakes.
[0013] Specifically, in step S4, the mass ratio of bisphenol A diglycidyl ether (DGEBA) to neopentyl glycol diglycidyl ether (NGDE) is 1:0.5~0.8; the amount of aminopropyl dimethylsiloxane (NH2-PDMS-NH2) added is 30%~50% of the mass of bisphenol A diglycidyl ether (DGEBA); and the amount of polyetheramine D230 curing agent added is 50%~80% of the mass of bisphenol A diglycidyl ether (DGEBA).
[0014] Specifically, in step S5, the amount of functional nanofiller BS@MN added is 5% to 15% of the total mass of the hydrophobic modified epoxy resin matrix PDMS-EP; the spin coating speed is 200 to 400 r / min and the time is 10 to 100 s; the curing conditions are room temperature curing for 8 to 16 h, followed by drying at 40 to 60 ℃ for 8 to 16 h.
[0015] This invention also provides a hydrophobically modified self-healing epoxy resin composite coating (PDMS-EP / BS@MN) prepared using the above-described method. The preparation process of this invention is simple, and the resulting coating exhibits excellent corrosion protection against magnesium alloys in strong acid, strong alkali, or neutral salt solutions, demonstrating outstanding environmental adaptability. After 50 days of exposure to salt spray, the surface of the coating remains intact, demonstrating good long-term corrosion resistance.
[0016] This invention also provides the application of the above-mentioned hydrophobic modified self-healing epoxy resin composite coating in metal corrosion protection.
[0017] Furthermore, in the above applications, the metal includes, but is not limited to, magnesium alloys, etc. When scratches occur on the coating surface, the [MCIM][NTf2] ionic liquid corrosion inhibitor loaded in the coating can form a protective film on the metal substrate surface, achieving active self-repair.
[0018] This invention discloses a hydrophobically modified self-healing epoxy resin composite coating: the coating uses hydrophobically modified epoxy resin (PDMS-EP) as the matrix and introduces basalt flakes (BS@MN) loaded with ionic liquid corrosion inhibitors as functional nanofillers to achieve both hydrophobicity and self-healing function. The composite coating prepared by this invention significantly improves the long-term corrosion resistance of magnesium alloys. The lamellar structure of basalt flakes (BS) forms a staggered arrangement, increasing the path and time for corrosive media to diffuse to the matrix resin. The introduction of PDMS reduces the surface energy of the coating and enhances hydrophobicity. When the coating is damaged, the ionic liquid corrosion inhibitor is released and forms a protective film at the corrosion site, achieving active repair. This synergistic effect of hydrophobic modification and active repair system provides magnesium alloys with dual protection combining "passive barrier" and "active repair." The preparation method is simple, and the resulting composite coating exhibits excellent long-term corrosion resistance and environmental adaptability, making it valuable for industrial scale-up applications.
[0019] Compared with the prior art, the present invention has the following advantages and beneficial effects: In this invention, the hydrophobically modified self-healing epoxy resin composite coating is easy to prepare. The added basalt flakes possess excellent sheet-like shielding effect and chemical inertness, effectively extending the diffusion path of corrosive media. The loaded ionic liquid corrosion inhibitor can release to form a protective film when the coating is damaged, achieving active self-healing. The coating of this invention exhibits good corrosion resistance and excellent self-healing properties, effectively improving the long-term corrosion resistance of magnesium alloys. Attached Figure Description
[0020] Figure 1 The TGA curves of the BS, [MCIM][NTf2] and BS@MN samples of this invention are shown.
[0021] Figure 2 This is a comparison diagram of the contact angles of the EP, PDMS-EP, and PDMS-EP / BS@MN coatings of the present invention.
[0022] Figure 3To obtain the Nyquist and Bode plots of the coating after different immersion times in 3.5 wt.% NaCl solution: a~c are the Nyquist plot, Bode impedance mode plot and Bode phase angle plot of the EP sample, respectively; d~f are the Nyquist plot, Bode impedance mode plot and Bode phase angle plot of the PDMS-EP sample, respectively; g~i are the Nyquist plot, Bode impedance mode plot and Bode phase angle plot of the PDMS-EP / BS@MN sample, respectively.
[0023] Figure 4 Results for EP, PDMS-EP, and PDMS-EP / BS@MN coatings in a 5.0 wt.% NaCl salt spray test.
[0024] Figure 5 The scratch immersion test results of EP, PDMS-EP and PDMS-EP / BS@MN coatings under different environments are as follows: a) strong acid solution (pH=2); b) strong alkali solution (pH=13); c) 3.5 wt.% NaCl solution. Detailed Implementation
[0025] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings and examples. The described embodiments are merely some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0026] Unless otherwise specified, all raw materials used in the following examples are commercially available products. For example, the aminopropyl dual-terminated polydimethylsiloxane used was purchased from Zhengzhou Alpha Chemical Co., Ltd., specification: 25 g; molecular weight: 2500. The basalt flakes were purchased from Yantai Huazheng Kexin Industrial Co., Ltd.; type: silver, 400 mesh.
[0027] Room temperature refers to (25±5) ℃. Example 1
[0028] 1. Pretreatment of magnesium alloys (1) Machining AZ31B magnesium alloy into a sample with dimensions of 1.5 cm × 1.5 cm × 0.5 cm, and coating the substrate with epoxy resin, leaving only a 1.5 cm × 1.5 cm working surface; (2) Grind with 180, 600, 1500 and 3000 grit sandpaper in sequence, and then polish with W3.5 diamond polishing paste; (3) Finally, use distilled water and anhydrous ethanol to ultrasonically clean for 10 min each, dry at room temperature and set aside.
[0029] 2. Alkali etching treatment of basalt flakes Weigh 3.5 g of basalt flakes (BS) and place them in a 250 mL polytetrafluoroethylene beaker. Add 100 mL of a 4 mol / L sodium hydroxide solution. Stir continuously for 2 h at 100 ℃ in an oil bath. After the reaction is complete, wash repeatedly with deionized water until pH is neutral, and dry in a vacuum drying oven for 12 h to obtain alkali-etched basalt flakes (BS-OH).
[0030] 3. Synthesis of Ionic Liquid Corrosion Inhibitors 1.64 g (20 mmol) of 1-methylimidazole and 5.3 g (20 mmol) of 11-bromoundecanoic acid were weighed and placed in a 250 mL round-bottom flask. 80 mL of tetrahydrofuran (THF) was added as a solvent, and the mixture was stirred at 40 °C for 24 h. After the reaction was completed, the mixture was washed with deionized water and dried to obtain a white solid [MCIM]Br.
[0031] Weigh 3.46 g (10 mmol) of [MCIM]Br and 3.16 g (11 mmol) of lithium bis(trifluoromethanesulfonyl)imide into a 100 mL round-bottom flask, add 40 mL of deionized water, and stir the mixture at 40 °C for 10 h. Remove the water by rotary evaporation, and dry to obtain a pale yellow ionic liquid corrosion inhibitor [MCIM][NTf2](MN).
[0032] 4. Preparation of functional nanofiller BS@MN 0.5 g of alkali-etched basalt flakes (BS-OH) were weighed and placed in a 150 mL round-bottom flask. 50 mL of THF was added, and the mixture was ultrasonically dispersed for 30 min. 1.5 g of ionic liquid corrosion inhibitor [MCIM][NTf2] was added, and the mixture was stirred at room temperature for 24 h. After the reaction was complete, the product was washed with anhydrous ethanol and vacuum dried for 12 h to obtain the functional nanofiller BS@MN.
[0033] like Figure 1 As shown in the TGA curve, the grafting amount of [MCIM][NTf2] on the BS surface is approximately 34.1%. Example 2
[0034] 1. Formulation of hydrophobically modified epoxy resin matrix Weigh 1.70 g of bisphenol A diglycidyl ether (DGEBA) and 1.08 g of neopentyl glycol diglycidyl ether (NGDE) into a beaker and sonicate for 15 min to mix thoroughly. Add 0.76 g of aminopropyl double-terminated polydimethylsiloxane (NH2-PDMS-NH2), followed by 1.15 g of polyetheramine D230 curing agent. Sonicate again for 15 min and stir for 10 h to obtain the hydrophobically modified epoxy resin matrix (PDMS-EP).
[0035] 2. Preparation of composite coatings 0.393 g of functional nanofiller BS@MN was added to the prepared hydrophobically modified epoxy resin matrix PDMS-EP (the amount of functional nanofiller BS@MN added was 10% of the total mass of the hydrophobically modified epoxy resin matrix). After ultrasonic dispersion for 15 min, the mixture was stirred for 2 h to obtain a uniformly dispersed suspension. Then, the suspension was coated onto the pretreated AZ31B magnesium alloy surface using a spin coater (300 rpm, 50 s). The coating was cured at room temperature for 12 h and then dried at 50 ℃ for 12 h to obtain the PDMS-EP / BS@MN composite coating.
[0036] Comparative Example 1
[0037] Pure EP coating is prepared as follows: Weigh 1.70 g DGEBA and 1.08 g NGDE, mix them, add 1.15 g D230 curing agent, stir for 10 min, spin coat the mixture onto the pretreated AZ31B magnesium alloy surface, cure at room temperature for 12 h, and dry at 50 ℃ for 12 h.
[0038] Comparative Example 2
[0039] The PDMS-EP coating is prepared as follows: Prepare PDMS-EP according to step 1 of Example 2, without adding BS@MN, and spin-coat and cure in the same way.
[0040] Figure 1 The thermal stability (TGA) curves of BS, [MCIM][NTf2], and BS@MN samples are presented. The figures show that BS exhibits excellent thermal stability with a mass loss rate of approximately 16.74% at 800℃; [MCIM][NTf2] decomposes rapidly between 300 and 500℃, with a mass loss rate exceeding 80%; the thermal decomposition behavior of the BS@MN composite material combines characteristics of both, with a significantly higher mass loss rate than BS in the 300–500℃ range, reaching approximately 50.84% at 800℃. By comparing the percentage mass loss of BS and BS@MN at 800℃, the grafting amount of [MCIM][NTf2] on the BS surface can be calculated to be approximately 34.1%.
[0041] Figure 2 Comparative photographs of the contact angles of EP, PDMS-EP, and PDMS-EP / BS@MN coatings are presented. The figures show that the pure EP coating has a contact angle of 76.2°, exhibiting hydrophilicity. After PDMS modification, the contact angle of the PDMS-EP coating increases to 114.6°, achieving a transformation from hydrophilic to hydrophobic. With the introduction of BS@MN, the contact angle of the PDMS-EP / BS@MN coating described in this invention further increases to 135.3°, indicating that the synergistic effect of PDMS and BS@MN significantly enhances the hydrophobicity of the coating.
[0042] Figure 3 Nyquist and Bode plots of EP, PDMS-EP, and PDMS-EP / BS@MN coatings in 3.5 wt.% NaCl solution are presented. The figures show that, compared to the EP and PDMS-EP coatings, the PDMS-EP / BS@MN composite coating exhibits the smallest changes in capacitive arc radius, low-frequency impedance modulus, and phase angle with increasing immersion time, indicating its superior long-term corrosion resistance.
[0043] Figure 4 Optical images of the surfaces of three coatings—EP, PDMS-EP, and PDMS-EP / BS@MN—after accelerated aging in a salt spray environment of 5 wt.% NaCl for different time periods. Salt spray accelerated aging tests, by simulating a highly corrosive environment, can effectively characterize the long-term corrosion resistance of coatings within a short period, providing a basis for evaluating the protective life of coatings. Figure 4 It can be seen that the EP coating showed no corrosion initially in the salt spray test, but corrosion began to appear at the coating edges after 26 days of neutral salt spray testing. After 35 days, a large area of corrosion appeared in the lower right corner of the coating, and the coating gradually peeled off as the test time increased. The PDMS-EP coating gradually darkened in color during immersion, and fine black corrosion spots appeared on the coating surface after 50 days, indicating that the corrosive medium had penetrated the coating and its corrosion resistance had deteriorated. The PDMS-EP / BS@MN composite coating described in this invention showed no significant changes on the coating surface throughout the entire 50-day test period, demonstrating excellent corrosion resistance and long-term protective stability.
[0044] Figure 5The results of scratch immersion tests on EP, PDMS-EP, and PDMS-EP / BS@MN coatings in pH=2, pH=13, and 3.5 wt.% NaCl solutions are presented. As shown in the figures, in an acidic environment (pH=2), the EP coating showed complete corrosion at the scratch site within 24 h and completely detached after 264 h; the PDMS-EP coating showed improved acid resistance, but significant blistering and detachment occurred after 252 h; while the PDMS-EP / BS@MN coating described in this invention remained intact throughout the entire 264 h immersion process, with no significant corrosion expansion at the scratch site. In an alkaline environment (pH=13), none of the three coatings showed significant failure within 372 h. In 3.5 wt.% NaCl solution, the EP coating showed localized corrosion points after 312 h and detached after 336 h; the PDMS-EP coating showed localized detachment after 372 h; while the PDMS-EP / BS@MN coating described in this invention remained intact for 372 h. The above results show that the PDMS-EP / BS@MN coating described in this invention exhibits optimal protective performance in acid, alkali, and salt corrosive environments. This is attributed to the synergistic mechanism of the physical barrier effect and active self-healing action of the composite coating.
[0045] In summary, the PDMS-EP / BS@MN composite coating prepared by this invention has excellent corrosion resistance, hydrophobicity, and active self-healing properties, and has broad application prospects in the field of magnesium alloy corrosion protection.
[0046] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the invention. The scope of protection of the present invention should be determined by the appended claims.
Claims
1. A method for preparing a hydrophobically modified self-healing epoxy resin composite coating, characterized in that, Includes the following steps: S1. Basalt flakes are placed in sodium hydroxide solution and stirred at 80~120 ℃ for 1~4 h. After washing and drying, basalt flakes with alkaline etching treatment are obtained. S2. 1-Methylimidazolium and 11-bromoundecanoic acid are reacted in an organic solvent at 30-50 °C for 20-28 h to obtain [MCIM]Br; then [MCIM]Br is reacted with lithium bis(trifluoromethanesulfonyl)imide in water at 30-50 °C for 8-12 h, and the mixture is then subjected to rotary evaporation and drying to obtain an ionic liquid corrosion inhibitor. S3. The basalt flakes obtained from step S1 and the ionic liquid corrosion inhibitor obtained from step S2 are mixed in tetrahydrofuran, stirred at room temperature for 20-28 h, washed and dried to obtain the functional nanofiller BS@MN. S4. Mix bisphenol A diglycidyl ether and neopentyl glycol diglycidyl ether evenly, add aminopropyl double-terminated polydimethylsiloxane and polyetheramine D230 curing agent, mix evenly to obtain hydrophobic modified epoxy resin matrix; S5. Add the functional nanofiller BS@MN obtained in step S3 to the hydrophobic modified epoxy resin matrix obtained in step S4, disperse it evenly, coat it onto the surface of the pretreated metal matrix by spin coating, cure it at room temperature, and dry it to obtain the final product.
2. The preparation method according to claim 1, characterized in that, The concentration of the sodium hydroxide solution in step S1 is 2~6 mol / L.
3. The preparation method according to claim 1, characterized in that, In step S2, the molar ratio of 1-methylimidazolium to 11-bromoundecanoic acid is 1:0.8~1.2; the molar ratio of [MCIM]Br to lithium bis(trifluoromethanesulfonylimide) is 1:0.8~1.2; and the organic solvent is tetrahydrofuran.
4. The preparation method according to claim 1, characterized in that, In step S3, the mass ratio of basalt flakes treated with alkali etching to ionic liquid corrosion inhibitor is 1:2~4.
5. The preparation method according to claim 1, characterized in that, In step S4, the mass ratio of bisphenol A diglycidyl ether to neopentyl glycol diglycidyl ether is 1:0.5~0.8; the amount of aminopropyl dimethylsiloxane added is 30%~50% of the mass of bisphenol A diglycidyl ether; and the amount of polyetheramine D230 curing agent added is 50%~80% of the mass of bisphenol A diglycidyl ether.
6. The preparation method according to claim 1, characterized in that, In step S5, the amount of functional nanofiller BS@MN added is 5% to 15% of the total mass of the hydrophobic modified epoxy resin matrix; the spin coating speed is 200 to 400 r / min and the time is 10 to 100 s.
7. A hydrophobic modified self-healing epoxy resin composite coating prepared by any of the preparation methods described in claims 1 to 6.
8. The application of the hydrophobic modified self-healing epoxy resin composite coating of claim 7 in metal corrosion protection.
9. The application as described in claim 8, characterized in that, The metal is a magnesium alloy.
